Suicide attempts and non-suicidal self-harm: a national prevalence study of young adults - O’Connor, Rory C.; Wetherall, Karen; Cleare, Seonaid; Eschle, Sarah; Drummond, Julie; Ferguson, Eamonn; O’Connor, Daryl B.; O'Carroll, Ronan E. (Royal College of Psychiatrists, 2018)
Background: There are few prevalence studies of suicide attempts (SAs) and non-suicidal self-harm (NSSH). Aims: This study aimed to estimate the prevalence of thoughts of NSSH, suicidal thoughts, NSSH and SAs among 18-34 year olds in Scotland for the first time. Method: We interviewed a representative sample of young adults from across Scotland. Results: 3508 young people were interviewed. 11·3% and 16·2% reported a lifetime history of SAs and NSSH, respectively. The first episode of NSSH tended to precede the first SA by about two years. Age of onset of NSSH and SA was younger in females. Earlier age of onset was associated with more frequent NSSH/SA. Women are significantly more likely to report NSSH and SA compared to men. Conclusion: One in 9 young people has attempted suicide and 1 in 6 has engaged in NSSH. Clinicians should be vigilant as SAs and NSSH are relatively common.